2012
DOI: 10.1149/1.4717956
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Variation of Electrodeposited Li in Ionic Liquid

Abstract: Li metal negative electrode is expected for the next-generation Li battery electrode material, and the control of morphological variation of the Li metal electrode surface is very important issue. In-situ observation of the Li dendrite growth in an ionic liquid by an optical microscope was done in order to discuss the relationship between the Li dendrite growth and the Li + ionic mass transfer rate. Li dendrite growth in the ionic liquid starts before the surface Li + ion concentration which is calculated by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…13,21 A schematic of the model domain is shown in Figure 1. The dendrite model simulation domain consists of the anode surface and the electrolyte, which acts as a stationary diffusion medium with a diffusion boundary layer of thickness L. 13,22 Note that the anode surface roughness is exaggerated in Figure 1 to emphasize the heterogeneous nucleation points on the anode surface. The Li + in the electrolyte react with electrons at the anode surface, and form dendrite structures on the anode surface.…”
Section: Numerical Model Of Anisotropic Transport At the Anode-electr...mentioning
confidence: 99%
“…13,21 A schematic of the model domain is shown in Figure 1. The dendrite model simulation domain consists of the anode surface and the electrolyte, which acts as a stationary diffusion medium with a diffusion boundary layer of thickness L. 13,22 Note that the anode surface roughness is exaggerated in Figure 1 to emphasize the heterogeneous nucleation points on the anode surface. The Li + in the electrolyte react with electrons at the anode surface, and form dendrite structures on the anode surface.…”
Section: Numerical Model Of Anisotropic Transport At the Anode-electr...mentioning
confidence: 99%
“…Recently, Li et al, showed that increasing the plating current density and, thereby, increasing the self-heating of the cell due to parastic heat losses may provide another mitigation strategy to suppressing dendrites. High current/rate performance of lithium–metal batteries is a critical requirement for fast charging. , Some literature reports find support for shorter dendrites at higher rates, while other reports suggest the opposite trend. Similarly, increasing of temperature has shown to lead to the growth of longer dendrites or poor performance, , while others report improved performance at higher temperature. These studies indicate that the high current/rate and high temperature properties of the lithium battery are rather complicated, which raises two key questions: (1) how to theoretically analyze the rate performance of a lithium–metal based battery and (2) under what conditions will lithium metal anodes be stable against high rate cycling. An increase in the temperature of the cell leads to numerous changes that all have an effect on the electrodeposition process: an increase in (i) the diffusion coefficient of lithium ions in the electrolyte, (ii) the electrochemical reaction rate, and (iii) the surface diffusion.…”
mentioning
confidence: 99%
“…Several interesting observations regarding Li dendrite formation have been observed by in situ optical microscopy in Li batteries . Though advanced phenomena, such as nucleation, could not be observed due to low magnifications, fundamental information regarding Li metal deposition and growth could be obtained.…”
Section: Optical Techniquesmentioning
confidence: 99%